اتجاهات تلاميذ المتوسط نحو مسار التكوين المهني - دراسة ميدانية ببعض متوسطات سيدي عامر بالمسيلة- - انسام بركات; عقيلة عيجولي; اشراف: كباهم خميسة (جامعة محمد بوضياف -المسيلة, 2025)
هدفت الدراسة إلى التعرف على طبيعة اتجاهات تلاميذ المرحلة المتوسطة نحو مسار التكوين المهني، بالإضافة إلى معرفة الفروق في الاتجاهات تبعا لمتغير الجنس لدى تلاميذ هذه المرحلة، ولتحقيق أهداف الدراسة تم الاعتماد على المنهج الوصفي باعتباره الأنسب لوصف الظاهرة المدروسة، وأداة استبيان، المكون من51 بندا موزعة على ثلاثة محاور (محور الاتجاه المعرفي، محور الاتجاه السلوكي، محور الاتجاه الوجداني)، وقد تم تطبيق الأداة على عينة قوامها (60) تلميذا وتلميذة يدرسون بأقسام السنة الرابعة متوسط بسيدي عامر ولاية المسيلة، وبعد المعالجة الإحصائية للبيانات أظهرت النتائج أن : • وجود اتجاهات إيجابية لتلاميذ المرحلة المتوسطة نحو مسار التكوين المهني. • عدم وجود فروق ذات دلالة إحصائية بين أفراد العينة في اتجاهات التلاميذ نحو مسار التكوين المهني تبعا لمتغير الجنس الكلمات المفتاحية: الاتجاهات، مسار التكوين المهني، تلاميذ المرحلة المتوسطة. Abstarct : The study aimed to identify the nature of middle school students' attitudes toward vocational training, as well as to identify differences in attitudes based on gender among students at this stage. To achieve the study's objectives, the descriptive approach was adopted, as it is the most appropriate method for describing the phenomenon under study. A questionnaire was used as a tool, consisting of 51 items distributed across three axes (cognitive orientation, behavioral orientation, and affective orientation). The tool was applied to a sample of (60) male and female students studying in the fourth-year middle school classes in Sidi Amer, M'Sila Province. After statistical processing of the data, the results showed that: • There were positive attitudes among middle school students toward vocational training. • There were no statistically significant differences among sample members in students' attitudes toward vocational training based on gender. Keywords: attitudes, vocational training, middle school students.